Public Audit and Governance Quality in Decentralized Systems: The Case of Indonesia - Siahay, Adolf Z. D.; Salle, Agustinus (Amkop Management Accounting Review (AMAR), 2025)
This study explores the relationship between audit opinions and governance weaknesses in Indonesian local governments from 2020 to 2024. Although most local governments received Unqualified Audit Opinions (UAO), many still face problems in areas such as Government Accounting Standards (GASB) compliance, Internal Control Systems (ICS), legal violations, poor financial disclosures, and lack of follow-up on audit recommendations (FAR). Using five years of national audit summary data from BPK, this research applies trend analysis and regression to see how these issues affect audit opinion scores. The results show that better compliance with government accounting standards and clear financial disclosures lead to better audit ratings. Legal violations reduce audit opinion quality. ICS has a negligible effect, while the FAR follow-up has little short-term impact. This study suggests that audit opinions do not always reflect the actual condition of financial governance. It recommends strengthening performance audits and improving how audit opinions are evaluated.